The effect of self-inflicted burns on ABSI score prediction power: A four-year prospective multicenter study of the German Burn Registry. Issue 7 (November 2022) - Billner, Moritz; Reif, Simon; Registry, German Burn; Reichert, Bert
Highlights: Self-inflicted burns (SIB)are associated with lower survival rates compared to accident related burns. Statistical analysis of 5330 patients showed a 6.8 percentage points lower survival rate for patients with SIB. Higher mortality rates in patients with SIB cannot be explained by severity of burn indicators used in the ABSI score. The modified score by Yamamoto et al. (2020) yields the best survival predictions for our sample. Abstract: Background: Suicide attempted by self-inflicted burns are associated with lower survival rates compared to accident related burns. Objective: We investigate the relation between self-inflicted burns (SIB) and survival rates and how this relation is moderated by variables used to predict survival rates in the ABSI score, a widely used measure. Additionally, we compare the predicted survival rates by the ABSI score to the actual rates in our sample for SIB and accident patients. Methods: In this prospective multicenter study data from the German Burn Registry are statistically analyzed using two sided t -test and multivariate linear regression models. Results: 5330 patients (214 with SIB) met our inclusion criteria. We find a 6.8 percentage points lower survival rate for patients with SIB when we control for patient condition with the five ABSI components as covariates. These higher mortality rates can be explained by the higher rate of therapy restrictions for patients with self-inflicted burns. Additionally, different ABSI modifications can improve the predictive power of the score. Conclusion: Patients with SIB have lower survival rates compared to accident patients. Recently proposed modifications of the ABSI score can improve the accuracy of survival rate prediction for SIB.